Estimation of serum immunoglobulins as a diagnostic marker in Oral Submucous Fibrosis (OSMF) patients - Ragini Gupta; Manu Dhillon; Soumendu B Maiti; Lalit Narayan Singh; Joy Lakhina; Arpan Manna (Wolters Kluwer Medknow Publications, 2022)
Introduction: Oral submucous fibrosis (OSMF) is a potentially malignant disorder affecting the oral mucosa, now accepted globally as a disease. The Indian subcontinent has high malignant transformation potential with multifactorial etiologies and unclear pathogenesis. Immunological pathogenesis has been hypothesized as a causative factor for oral submucous fibrosis. Aim: To quantitatively evaluate IgG and IgM in serum of oral submucous fibrosis, thereby observing any possible association of these immunoglobulins in the pathogenesis of this disease. Material and Methods: A case-control study was done among 60 subjects, including 30 patients with clinically confirmed OSMF and 30 in the control group. Two milliliters of blood was collected from both groups. Quantitative analysis of serum IgG and IgM was done by turbidometric immunoassay. The results were analyzed by unpaired student's t-test and one-way analysis of variance (ANOVA). Results: All patients of OSMF showed increased serum IgG compared to the control group, and the differences were found to be statistically significant (P >.05). On comparing IgM levels between the control and study group, differences were statistically nonsignificant (P < 0.457). Conclusion: The elevation of immunoglobulin levels supports the concept of autoimmunity.